2016
DOI: 10.1136/gutjnl-2016-312201
|View full text |Cite
|
Sign up to set email alerts
|

An evidence-based treatment algorithm for colorectal polyp cancers: results from the Scottish Screen-detected Polyp Cancer Study (SSPoCS)

Abstract: A policy of surveillance is adequate for the majority of patients with screen-detected colorectal polyp cancers. Consideration of segmental resection should be reserved for those with incomplete excision or evidence of lymphovascular invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 28 publications
2
50
0
Order By: Relevance
“…A study of the Scottish Surgical Research Group on 485 patients with T1CRCs, which were identified through the screening program between 2000 and 2012, found no significant difference in adverse outcomes between pedunculated and nonpedunculated T1CRCs after adjustment for confounders. 34 However, this study only included patients who underwent endoscopic resection (followed by segmental resection or not), which may have led to exclusion of nonpedunculated high-risk T1CRCs unfit for endoscopic resection in particular, leading to an underestimation of adverse outcomes in the nonpedunculated T1CRC group.…”
Section: Discussionmentioning
confidence: 99%
“…A study of the Scottish Surgical Research Group on 485 patients with T1CRCs, which were identified through the screening program between 2000 and 2012, found no significant difference in adverse outcomes between pedunculated and nonpedunculated T1CRCs after adjustment for confounders. 34 However, this study only included patients who underwent endoscopic resection (followed by segmental resection or not), which may have led to exclusion of nonpedunculated high-risk T1CRCs unfit for endoscopic resection in particular, leading to an underestimation of adverse outcomes in the nonpedunculated T1CRC group.…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence is now accumulating that such a clearance may not be necessary as long as the distance between the invasive front and resection margin can be assessed and accurately measured. For example, a national cohort study in Scotland reported that a “positive” polyp resection margin was only associated with residual disease in the bowel wall if tumor cells extended into the diathermy burn zone. Similarly, updated national guidelines in Japan now state that the vertical margin of an MCP should only be considered positive if carcinoma is exposed at the submucosal margin …”
Section: Introductionmentioning
confidence: 99%
“…This 10% rate of "residual disease" postpolypectomy of pT1 cancer is broadly that to be anticipated. Richards and colleagues advise segmental resection in cases of incom-plete resection or evidence of lymphovascular invasion (16). The presence of tumor budding may in the future be an additional indicator of potential nodal involvement in these early cancers (17).…”
Section: Discussionmentioning
confidence: 99%